2013
DOI: 10.1007/s11523-013-0254-0
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines associated with toxicity in the treatment of recurrent glioblastoma with aflibercept

Abstract: Plasma profiling of patients treated with antiangiogenic agents may identify markers that correlate with toxicity. Objectives were to correlate changes in cytokine and angiogenic factors as potential markers of toxicity to aflibercept. Circulating cytokine and angiogenic factors were measured in 28 patients with recurrent glioblastoma in a single-arm phase II study of aflibercept. Plasma samples were analyzed at baseline, 24 h, and 28 days using multiplex assays or ELISA. We evaluated log-transformed baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Less is known about the role of IL-13 in glioblastoma biology. A recent clinical study demonstrated that changes in plasma IL-13 levels, during patient treatment with a novel anti-angiogenic agent, were associated with increased on-target toxicities [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Less is known about the role of IL-13 in glioblastoma biology. A recent clinical study demonstrated that changes in plasma IL-13 levels, during patient treatment with a novel anti-angiogenic agent, were associated with increased on-target toxicities [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, plasma profiling of patients treated with the antiangiogenic agent aflibercept in 28 patients with recurrent GBM revealed that changes in IL-13 from baseline to 24 h predicted on-target toxicities. Increases in IL-1β, IL-6, and IL-10 at 24 h were significantly associated with fatigue [142].…”
Section: Cytokines Associated With Toxicity In Glioma Patientsmentioning
confidence: 90%
“…They can generate cytokines including interleukin-10 (IL-10) and transforming growth factor-beta (TGF-β), which suppress the activity of immune cells like T-cells and NK cells while promoting GB development and invasion (Garg et al, 2017;Jiao et al, 2017). Furthermore, B cells can secrete pro-angiogenic factors such as VEGF, CXC chemokine ligand 12 (CXCL12), and CXC chemokine ligand 13 (CXCL13), which stimulate the formation of new blood vessels, provide nutrients and oxygen to the tumor, and promote GB growth and invasion (Shonka et al, 2013).…”
Section: B Cellsmentioning
confidence: 99%